Axillary sentinel node biopsy in prone position for melanomas on the upper back or nape. Issue 4 (4th July 2019) - Kretschmer, Lutz; Hellriegel, Simin; Cevik, Naciye; Hartmann, Franziska; Thoms, Kai-Martin; Schön, Michael P.
Abstract: In patients with melanomas on the upper back or nape, axillary sentinel lymph node (SLN) biopsy (SLNB), when performed in the traditional supine position, is often disturbed by scattered radiation emitted from the primary tumor site. The results from the present study suggestthat axillary SLNB performed in the prone position can solve this problem. We compared two consecutive groups of patients with melanomas of the dorsal trunk or nape who received axillary SLNB performed either in the supine ( n  = 119) or in the prone position ( n  = 130). The number of SLNs detected and excised was significantly higher in prone position group (2.4 ± 1.5 SLNs versus 1.9 ± 0.95 SLNs, p  = 0.002). Using the prone position, intra-operative repositioning of the patient for excision of a primary site of the upper back or neck was not necessary. The SLN identification rates and the SLN-positivity rates did not differ significantly between the two types of intraoperative patient positioning. There were no significant differences in survival outcomes or false-negative rates. In conclusion, axillary SLNB in prone position yields a higher number of excised SLNs in patients with melanomas of the upper back or nape. Axillary SLNB in prone position is easy to perform and reliable. Intraoperative repositioning of the patient is not necessary, which saves time and resources.